The realization of integrated marketing communications that affect purchasing behaviors of adolescent girl cosmetics in Bangkok - Thongrod, Chairit (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
In this thesis, the researcher investigated (1) to study perceptions of integrated marketing communication affecting the buying behavior of adolescent girl cosmetics in Bangkok (2) recognition of integrated marketing communications affecting the buying behavior of adolescent girl cosmetics in Bangkok. By personal appearance and (3) to analysis confirmatory factor analysis of the recognition of integrated marketing communications affecting the buying behavior of adolescent girl cosmetics in Bangkok. Targeted population in this research context was the Thai adolescent girl age between 15-20 years in Bangkok metropolitan. Using a two-stage sampling method first the simple random sampling. Drawing list at the underground train for 4 stations, moreover at the sky train for 4 stations. Second accidental sampling collected data from an adolescent girl at each station for 53 samples by the end of 424 the total cases. With regard to research methodology, researcher developed questionnaire testing content validity and reliability of the data prior to analysis. The statistics analytical techniques was used by the researcher which consisting of percentage, t- test, one-way ANOVA and second order confirmatory factor analysis with LISREL program. Research findings revealed that respondents were aged 16 years (31.4 percentage), experienced using of foreign cosmetics (65.3 percentage), purchase prices of cosmetics in the price 501-999 baht per piece (52.4 percentage). Result from the study of the perception of integrated marketing communications to influence the buying behavior of adolescent girl cosmetics in Bangkok in the overall level is extreme (mean = 4.11). When sorting the average of most to least likely to find that the perception of an integrated marketing communications based on public relations, advertising and marketing activities, the promotion and direct marketing respectively. Recognition of integrated marketing communications to influence the buying behavior of adolescent girl cosmetics in Bangkok number of establishments by personal appearance. The results showed that: (1) perceptions of integrated marketing communications between ever use and never use abroad cosmetics are a significant statistical difference in overall and differences in the advertising, promotion, selling and the direct marketing. (2) perceived integration between marketing communications. The age difference was statistically significant in the overall field of advertising, selling, promotion and direct marketing. (3) recognition of integrated marketing communications between users who buy cosmetics at a different time, a significant statistical overview on the advertisement, the marketing promotion, direct marketing and event marketing. A confirmatory factor analysis result using LISREL program found that recognition of integrated marketing communications to influence the buying behavior of adolescent girl cosmetics in the Bangkok area, depending on the advertising campaign (Y = 0.89), the promotion (Y = 0.86), marketing activities (Y = 0.85), the direct marketing (Y = 0.85) and public relations (Y = 0.77 respectively. Article history : Accepted 5 May 2014 SIMILARITY INDEX = 2.94